2015
DOI: 10.5536/kjps.2014.42.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Quercetin on Growth Performance, Blood Biochemical Parameter, Immunoglobulin and Blood Antioxidant Activity in Broiler Chicks

Abstract: This study was conducted to investigate the effects of dietary quercetin on growth performance, blood biochemical parameters, immunoglobulin, and blood antioxidant activity in broiler chickens. Three hundred twenty one-day old Ross broilers were divided 8 treatments (C(-), basal diet; C(+), basal diet with antibiotics; vitamin E 20 IU; vitamin E 200 IU; quercetin 20 ppm; quercetin 200 ppm; methoxylated quercetin 20 ppm; methoxylated quercetin 200 ppm) with 4 replicates and 10 birds per replicate. Birds were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
2
11
1
Order By: Relevance
“…Flavonoids such as quercetin (bioactive compound of POLM), which is a flavone, enhance the secretion of insulin-like growth factor-1, which results due to the increased concentration of growth hormone and stimulation of hepatic growth hormone receptor [ 65 ]. Thus, the supplementation of quercetin improved production performance in broilers [ 66 ]. In the present study, broilers fed on the diet Po8 showed increased growth performance compared to the NC group; these outcomes are parallel to Aroche et al [ 67 ] and Zhou et al [ 68 ] where they reported that supplementation of PFAs mix powder and baicalein flavonoids resulted in increased BWG and improved FCR in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids such as quercetin (bioactive compound of POLM), which is a flavone, enhance the secretion of insulin-like growth factor-1, which results due to the increased concentration of growth hormone and stimulation of hepatic growth hormone receptor [ 65 ]. Thus, the supplementation of quercetin improved production performance in broilers [ 66 ]. In the present study, broilers fed on the diet Po8 showed increased growth performance compared to the NC group; these outcomes are parallel to Aroche et al [ 67 ] and Zhou et al [ 68 ] where they reported that supplementation of PFAs mix powder and baicalein flavonoids resulted in increased BWG and improved FCR in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is a flavone that should improve growth in birds by upregulating growth hormone, triggering the hepatic growth hormone receptor; this stimulus increases the concentration of insulin-like growth factor-1 [ 39 ]. Kim et al [ 40 ] reported increased broiler growth by supplementing quercetin in broilers. Quercetin can limit the effects of oxidative stress [ 41 ] and pro-inflammatory cytokines such as TNF-α, interleukin, and cyclooxygenase-2 [ 42 ], thus modulating the gut environment to better utilise the nutrients, improving the growth in birds.…”
Section: Discussionmentioning
confidence: 99%
“…In broilers, the supplementation of 0.2 g/kg of quercetin promoted growth and WG (Kim et al, ). Tilapia, Oreochromis niloticus fed diets containing 0.2–0.8 g/kg (J. Li, Liu, et al, ) or 0.2–1.6 g/kg (Zhai & Liu, 2013) of quercetin showed significantly higher WG and lower FCR than the control fish.…”
Section: Discussionmentioning
confidence: 99%
“…In broilers, the supplementation of 0.2 g/kg of quercetin promoted growth and WG (Kim et al, 2015). Tilapia, Note: Values in the same row with different letters indicate significant differences (p < .05) (n = 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation